Squire - Pierce, Tamora (New York Random House, 2001)
After becoming a squire to Lord Raoul, commander of the King's Own, Kel of Mindelan, must face a terrifying test in the Chamber of the Ordeal before she can be a knight.
Sequel to: Page.
Keywords: Knights and knighthood -- Fiction; Sex role -- Fiction; Fantasy